Rare benign lung tumours presenting with high clinical suspicion for malignancy: a case series and review of the literature - Popovic, Katarina; Miladinović, Mirjana; Vučković, Ljiljana; Nedović Vuković, Mirjana (Folia histochemica et cytobiologica, 2023)
Incidentally discovered lung nodules can be worrisome for both the patient and their physicians. Although 95% of solitary lung nodules are benign, it is important to distinguish which nodules have high clinical suspicion for malignancy. Existing clinical guidelines do not apply to patients with signs and symptoms related to the lesion and with an increased baseline risk of lung cancer or metastasis. This paper highlights the vital role of pathohistological analysis and immunohistochemistry in the definitive diagnosis of such incidentally discovered lung nodules. The three cases presented were selected based on their similar clinical presentations. A review of the literature was performed using the online database PubMed, for articles published in the period between January of 1973 to February of 2023 using the following medical subject headlines: "primary alveolar adenoma," "alveolar adenoma," "primary pulmonary meningioma," "pulmonary meningioma," and "pulmonary benign metastasizing leiomyoma." Results (Case Series). The case series consists of three incidentally discovered lung nodule(s). Although they presented with high clinical suspicion for malignancy, detailed workup confirmed the diagnosis of three rare benign lung tumours: primary alveolar adenoma, primary pulmonary meningioma, and benign metastasizing leiomyoma. Clinical suspicion for malignancy in the presented cases arose from previous and current medical history of malignancy, family history of malignancy, and/or specific radiographic findings. This paper highlights the need for a multidisciplinary approach in the management of incidentally discovered pulmonary nodules. Excisional biopsy and pathohistological analysis remain the gold standard in confirming the presence of a pathologic process and determining the nature of the disease. Common features of the diagnostic algorithm utilized among the three cases include multi-slice computerized tomography, excisional biopsy via atypical wedge resection (if the nodule is peripherally located), and lastly, pathomorphological analysis using haematoxylin and eosin staining and immunohistochemistry.